Ergovaline stability in tall fescue based on sample handling and storage methods - Lea, Krista; Smith, Lori; Gaskill, Cynthia; Coleman, Robert; Smith, S. Ray (Frontiers in Chemistry, 2014)
Ergovaline is an ergot alkaloid produced by the endophyte Neotyphodium coenophialum (Morgan-Jones and Gams) found in tall fescue (Schedonorus arundinacea (Schreb.) Dumort.) and blamed for a multitude of livestock disorders. Ergovaline is known to be unstable and affected by many variables. The objective of this study was to determine the effect of sample handling and storage on the stability of ergovaline in tall fescue samples. Fresh tall fescue was collected from a horse farm in central Kentucky at three harvest dates and transported on ice to the University of Kentucky Veterinary Diagnostic Laboratory. Plant material was frozen in liquid nitrogen, milled and mixed before being allocated into different sub-samples. Three sub-samples were assigned to each of 14 sample handling or storage treatments. Sample handling included increased heat and UV light to simulate transportation in a vehicle and on ice in a cooler per standard transportation recommendations. Storage conditions included storage at 22oC, 5oC and -20oC for up to 28 days. Each sub-sample was then analyzed for ergovaline concentration using HPLC with fluorescence detection and this experiment was repeated for each harvest date. Sub-samples exposed to UV light and heat lost a significant fraction of ergovaline in 2 hours, while sub-samples stored on ice in a cooler showed no change in ergovaline in 2 hours. All sub-samples stored at 22oC, 5oC and -20oC lost a significant fraction of ergovaline in the first 24 hours of storage. There was little change in ergovaline in the freezer (-20oC) after the first 24 hours up to 28 days of storage but intermittent losses were observed at 22oC and 5oC. To obtain results that most closely represent levels in the field, all samples should be transported on ice to the laboratory immediately after harvest for same day analysis. If immediate testing is not possible, samples should be stored at -20oC until analysis.